Repellent Activity of the Essential Oil from the Heartwood of Pilgerodendron Uviferum (D. Don) Florin Against Aegorhinus Superciliosus (Coleoptera: Curculionidae) - Urzua-Moll, A; Espinoza-Maldonado, J (Multidisciplinary Digital Publishing Institute (MDPI), 2016)
The weevil Aegorhinus superciliosus Guérin (Coleoptera: Curculionidae), which is endemic to Central-Southern Chile and Argentina, is one of the major berry pests in Chile and the most important pest in the La Araucanía Region (38°44 9"S, 72°35 25"W). Due to the poor effectiveness and problems surrounding the implementation of the traditional control methods using organophosphate and carbamate insecticides, new strategies for controlling this pest are needed. In this communication, we evaluated the behavioral responses of male and female A. superciliosus to volatile compounds released from the essential oil (EO) obtained from the heartwood of Pilgerodendron uviferum (D. Don) Florin using olfactometric bioassays. The composition of the EO was analyzed using gas chromatography (GC) and gas chromatography/mass spectrometry (GC/MS). According to these analyses, δ-cadinol (24.16%), cubenol (22.64%), 15-copaenol (15.46%) and δ-cadinene (10.81%) were the principal components of the EO. The Pilgerodendron uviferum EO, which is almost exclusively composed of sesquiterpenes (99.5%), exhibited a repellent effect against A. superciliosus adults, regardless of the sex or concentration used (56.6 mg/cm3 and 1.58×10-2 mg/cm3 ). The EO has low volatility and greater persistence than the EOs composed of monoterpenes and is considered a good model in the search for raspberry weevil repellents. © 2016 by the authors.